Efficient quantum simulation of photosynthetic light harvesting. (December 2018) - Wang, Bi-Xue; Tao, Ming-Jie; Ai, Qing; Xin, Tao; Lambert, Neill; Ruan, Dong; Cheng, Yuan-Chung; Nori, Franco; Deng, Fu-Guo; Long, Gui-Lu
Abstract Near-unity energy transfer efficiency has been widely observed in natural photosynthetic complexes. This phenomenon has attracted broad interest from different fields, such as physics, biology, chemistry, and material science, as it may offer valuable insights into efficient solar-energy harvesting. Recently, quantum coherent effects have been discovered in photosynthetic light harvesting, and their potential role on energy transfer has seen the heated debate. Here, we perform an experimental quantum simulation of photosynthetic energy transfer using nuclear magnetic resonance (NMR). We show that anN -chromophore photosynthetic complex, with arbitrary structure and bath spectral density, can be effectively simulated by a system with log2 N qubits. The computational cost of simulating such a system with a theoretical tool, like the hierarchical equation of motion, which is exponential inN, can be potentially reduced to requiring a just polynomial number of qubitsN using NMR quantum simulation. The benefits of performing such quantum simulation in NMR are even greater when the spectral density is complex, as in natural photosynthetic complexes. These findings may shed light on quantum coherence in energy transfer and help to provide design principles for efficient artificial light harvesting. Quantum simulations: Quantum effects in natural light harvesting Quantum simulations could unlock the role of quantum effects in photosynthesis. Energy transfer in natural photosynthetic complexes is extremely efficient, but it's not clear how such efficient energy transfer occurs. Quantum effects could potentially be playing an important role, but this remains a controversial area. An international collaboration led by Gui-Lu Long from Tsinghua University, Beijing National Research Center on Information Science and Technology and the Innovation Center of Quantum Matter now provide a proof-of-principle experiment showing that photosynthetic energy transfer can be simulated using quantum computers. Quantum simulations of this type should enable deeper investigations into the role of quantum effects in photosynthetic light harvesting, which could guide the design of artificial light harvesting devices.